"You have to be mental to jump off a board any way": Elite divers' conceptualizations and perceptions of mental health. (March 2017) - Coyle, Melissa; Gorczynski, Paul; Gibson, Kass
Abstract: Objectives: Mental health research in elite sport focuses predominantly on mental illness prevalence rates and help-seeking behaviours. Diving has been identified as a sport that generates particular challenges for maintaining mental health, yet has received scant attention from researchers. Therefore, purpose this paper explores what mental health and mental health related behaviours mean for a group of young, elite athletes as conditioned by their peculiar social context as elite athletes. Method: Semi-structured interviews were conducted with purposely sampled eight elite divers aged between 14 and 24 years with between 5 and 16 years of diving experience who have competed in international level diving competitions including Olympic, Common Wealth and World Cup competitions. Interviews were recorded, transcribed verbatim, and analyzed using inductive thematic analysis. Results: Analysis identified mental health literacy, experiences of mental health, risk factors, and opportunities for support as themes. Mental health generated negative connotations for participants attributable to knowledge development occurring through personal and vicarious experience of mental illness. Limited knowledge of symptoms of mental illnesses was evident. Participants identified a range of risk-factors inherent in their sport performance and culture revealing a performative and gendered dimension to mental health. Conclusions: Our results indicate the need to recognize the performative nature of mental health for elite divers and therefore social and cultural influences alongside biophysical. Greater efforts need to be made to help improve the overall mental health literacy of elite divers so they may be able to seek the support and treatment they need. Highlights: We examined elite divers' understanding of mental health and illness. Divers demonstrated limited mental health knowledge, but wanted to receive more information. Divers described being mentally healthy as performative in nature. Mental health risks for divers are produced by environmental and psychological factors.